Examining Culturally Responsive Education in Turkey through Strategic Plans - Gurkan SARİDAS; Funda NAYIR (Anı Publishing, 2022)
The strategic plan, which specifies the activities planned to be achieved by an institution in a certain period of time, is very important for the future actions of the institution. The purpose of this research was to find out culturally responsive educational activities in Turkey as specified in the strategic plans prepared by Ministry of National Education, and national education directorates at province and district level. Within the scope of the research, the 2019-2023 strategic plans of 72 school directorates (12 provinces and 36 districts) as well as the Ministry of National Education were examined in terms of culturally responsive education. In this descriptive qualitative study, document analysis method was used. According to the findings of the research, it was understood that culturally responsive education practices were not included enough in the strategic plans, and foreign students were mentioned in the section of weakness, risk or threat. Similarly, targets that would either increase the enrolment rate of foreign students or ensure the academic and social development of foreign students were not encountered in the strategic plans. It is suggested that, culturally responsive educational practices should be included in strategic plans.